THE EFFECT OF COMIC AS AN INTRODUCTION MEDIA OF BALI CATTLE IN UNIVERSITAS BRAWIJAYA - Siti Azizah; Ardan Legenda de Arham; Anie Eka Kusumastuti (Erudio Journal of Educational Innovation, 2019)
ABSTRACT Comic is mass media that convey[ALA1]  its contents through pictures and writings. The purpose of this research is to find out Universitas Brawijaya students’ knowledge change regarding Bali cattle after receiving comic intervention as a media exposure. The research design used is a true experimental design. Research conducted to 100 students using a questionnaire before and after intervention. The statistic test used in this research is the Wilcoxon test. Result shows there is an average value improvement in post-test compared with pre-test in comic group (P < 0.05). Also, it is found higher knowledge average values in a comic group compared with the website group (P < 0.05). Therefore, comic can be considered as an effective media in delivering knowledge about Bali cattle. [ALA1]Please check the grammar as a whole.